Desenvolvimento de uma centrífuga de alta rotação eletronicamente monitorada para pesquisa em biologia espacial - Nava, Marcelo José Anghinoni (2012)
This work presents the development of an centrifuge prototype for experiments with vegetables. Its main features are the high mechanical performance and instruments. In more details are presented the specification, implementation, validation and performance assessment through a case study. Its high speed and stability generates a vector component of centrifugal force, simulating conditions of hypergravity up to 15 times greater than the acceleration force on Earth. Plants subjected to the force have their metabolism modified. The system allows the study and monitoring of those growth patterns, showing how the samples are influenced by that stimulus induced on plants. The developed device has three levels of trays connected to a central axis, allowing the placement of 36 samples of containers simultaneously. Systems for remote monitoring of temperature, humidity and acceleration were developed and installed, ensuring uniformity of data. The transmission of these data was performed by radiofrequency. In addition, two independent systems of recording and transmission of images through VHF waves were created to determine the exact time of the plant growth stages (such as onset time of seeds and cotyledons formation). Once these components have been installed in the upper tray of the centrifuge, and were subjected to rotational movement, its power supply was provided through an external electrical source. In order to ensure the transmission of electric current between the static and dynamic part, it was employed a rotating two-pole connector. It was also developed a plate voltage regulator to deliver the correct voltage to each component. Finally, it was performed some performance tests and a comparative case study.